Development of the SciRAP Approach for Evaluating the Reliability and Relevance of in vitro Toxicity Data - Roth, Nicolas; Zilliacus, Johanna; Beronius, Anna (Frontiers in Toxicology, 2021)
Efficient and successful integration of data generated from non-animal test methods must rely on reliable and relevant data. It is important therefore to develop tools and criteria that facilitate scientifically sound, structured, and transparent evaluation of reliability and relevance of in vitro toxicity data to efficiently inform regulatory hazard and risk assessment. The Science in Risk Assessment and Policy (SciRAP) initiative aims to promote such overarching goals. We present the work to develop and refine the SciRAP tool for evaluation of reliability and relevance of in vitro studies for incorporation on the SciRAP web-based platform (www.scirap.org). In the SciRAP approach, reliability evaluation is based on criteria for reporting quality and methodological quality, and is explicitly separated from relevance evaluation. The SciRAP in vitro tool (version 1.0) was tested and evaluated during an expert test round (April 2019-September 2020) on three in vitro studies by thirty-one experts from regulatory authorities, industry and academia from different geographical areas and with various degree of experience in in vitro research and/or human health risk assessment. In addition, the experts answered an online survey to collect their feedback about the general features and desired characteristics of the tool for further refinement. The SciRAP in vitro tool (version 2.0) was revised based on the outcome of the expert test round (study evaluation and online survey) and consists of 24 criteria for evaluating ‘reporting quality’ (reliability), 16 criteria for ‘methodological quality’ (reliability), and 4 items for evaluating relevance of in vitro studies. Participants were generally positive about the adequacy, flexibility, and user-friendliness of the tool. The expert test round outlined the need to (i) revise the formulation of certain criteria; (ii) provide new or revised accompanying guidance for reporting quality and methodological quality criteria in the ‘test compounds and controls’, ‘test system’ and ‘data collection and analysis’ domains; and (iii) provide revised guidance for relevance items, as general measures to reduce inter-expert variability. The SciRAP in vitro tool allows for a structured and transparent evaluation of in vitro studies for use in regulatory hazard and risk assessment of chemicals.